Risk Profile of Symptomatic Lacunar Stroke Versus Nonlobar Intracerebral Hemorrhage. Issue 8 (August 2016) - Morotti, Andrea; Paciaroni, Maurizio; Zini, Andrea; Silvestrelli, Giorgio; Del Zotto, Elisabetta; Caso, Valeria; Dell'Acqua, Maria Luisa; Simone, Anna Maria; Lanari, Alessia; Costa, Paolo; Poli, Loris; De Giuli, Valeria; et al.
Abstract : Background and Purpose—: Although lacunar stroke (LS) and deep intracerebral hemorrhage (dICH) represent acute manifestations of the same pathological process involving cerebral small vessels (small vessel disease), it remains unclear what factors predispose to one phenotype rather than the other at individual level. Methods—: Consecutive patients with either acute symptomatic LS or dICH were prospectively enrolled as part of a multicenter Italian study. We compared the risk factor profile of the 2 subgroups using multivariable logistic regression. Results—: During a time course of 9.5 years, 1931 subjects (1434 LS and 497 dICH; mean age, 71.3±13.3 years; males, 55.5%) qualified for the analysis. Current smoking was associated with LS (odds ratio [OR], 2.17; P <0.001). Conversely, dICH cases were more likely to be hypertensive (OR, 1.87; P <0.001), excessive alcohol consumers (OR, 1.70; P =0.001), and more frequently under treatment with warfarin (OR, 2.05; P =0.010) and statins (OR, 3.10; P <0.001). Hypercholesterolemia, diabetes mellitus, and antiplatelet treatment were not associated with a specific small vessel disease manifestation. Conclusions—: The risk factor profile of dICH differs from that associated with LS. This might be used for disease risk stratification at individual level. Abstract : Supplemental Digital Content is available in the text.